Identification of the Heptapeptide PR7 and Octapeptide SF8 With Potent Antioxidative and Angiotensin Converting Enzyme Inhibitory Activity From the Fermented Dairy By-Product “Buttermilk” - Magouz, Osama; Ibrahim, Mahmoud A.A.; Mehanna, Nabil; Gensberger-Reigl, Sabrina; Dalabasmaz, Sevim; Pischetsrieder, Monika (Food Frontiers, 2024)
The present study aimed to identify antioxidative and angiotensin converting enzyme (ACE) inhibitory peptides in fermented buttermilk after simulated gastric digestion. Following isoelectric focusing fractionation, peptides of the most active fractions were identified by ultrahigh performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS). Subsequently, 23 peptides were synthesized and tested for antioxidative and ACE inhibitory activity. The peptide PR7 (PWDQVKR, αs2-casein 108–114) exerted comparable antioxidative activity to ascorbic acid, whereas the peptide SF8 (SGPLRPFF, butyrophilin 427–434) efficiently inhibited ACE with an IC50 value of 1.57 µM. The binding modes of the five most active ACE inhibitors were predicted using AlphaFold2 multimer software. Molecular mechanics (MM) minimization and molecular dynamics (MD) simulations of all complexes, followed by MM-generalized born surface area (GBSA) binding energy calculations, were predicted. Notably, these peptides manifested good binding affinities to ACE. The estimated MM-GBSA/MD binding energies correlated with the detected IC50 values [correlation coefficient (R2) = 0.79]. Post-MD analyses over 100 ns elucidated the steadiness of the five peptides.
CRIS-Team Scopus Importer:2025-02-04
Keywords: antioxidant and ACE inhibitory peptides; fermented buttermilk; molecular dynamics (MD) simulations; molecular mechanics (MM) minimization; PWDQVKR; SGPLRPFF